Tổng hợp và nghiên cứu đặc trưng của Cu2O kích thước nan - Độ, Vũ Đăng; Nguyệt, Triệu Thị; Sơn, Phạm Anh; Lụa, Nguyễn Thị; Hải, Nguyễn Minh (Vietnam Journal of Chemistry, 2014)
The nano-sized Cu2O particles are synthesized by wet method in which CuCl2is reduced by hydrazine in the presence of a surfactant (PVA or PEG or LA). The products are identified by X-Ray power diffraction (XRD), Transmission Electronic Microscope (TEM), High Resolution Transmission Electronic Microscope (HRTEM). The results showed that with suitable conditions, size of Cu2O particles is about 20 nm and diameter of Cu2O wire is about 15 nm.